Developing the Design Assumptions of Robotic Process Automation Maturity Model - Andrzej SOBCZAK (Communications of International Proceedings, 2020)
As weight of robotic process automation (RPA) increases, enterprises that implemented this approach should periodically perform a review and assessment of solutions applied – organizational and technological ones – and business benefits obtained. It should be conducted in systematized manner and include multiple factors. In particular, it should cover degree to which approach applied is aligned with organization’s strategic goals, how efficiently activities related to robotic process automation are performed on operational level (during software robot development and maintenance), or finally – what the personnel’s skill level and knowledge of robotic process automation is. If areas where improvements to the approach are necessary are identified, required improvement measures should be defined and implemented. Maturity models concept can be used to ensure systematized, complete approach to the review and assessment of approach to robotic process automation. Objectives of this article include: (G1) presenting key concepts of maturity models, (G2) analyzing existing approaches of robotic process automation maturity model for organizations, and (G3) defining the design assumptions of the proprietary robotic process automation maturity model, taking into account the imperfections and shortcomings of the existing approaches in this respect.
Keywords: Maturity Model; Robotic Process Automation; RPA; Robotic Process Automation Maturity Model